The subtle knife - Pullman, Philip, 1946- (New York : Ballantine Books, 1998)
As the boundaries between worlds begin to dissolve, Lyra and her daemon help Will Parry in his search for his father and for a powerful, magical knife.
Sequel to: The golden compass.
Notable/Best Books (A.L.A.).
Wilson's Junior High School.
Wilson's Senior High School.
7.6.
7.6
Keywords: Fantasy; Interplanetary voyages -- Fiction; Interplanetary voyages -- Fiction; Fantastic fiction